2009
DOI: 10.1142/s0192415x09006904
|View full text |Cite
|
Sign up to set email alerts
|

Water Extract ofGlycyrrhiza uralensisInhibited Enterovirus 71 in a Human Foreskin Fibroblast Cell Line

Abstract: Human infection by enterovirus type 71 (EV71) can cause life-threatening meningo-encephalitis. Currently, there is no effective anti-EV71 therapy available. Since EV71 infection commonly involves skin lesions, we tested our hypothesis that water extract of Glycyrrhiza uralensis (G. uralensis) could inhibit the cytopathic effects of EV71 in a human foreskin cell line by using an XTT-based method. Our results showed that the water extract of G. uralensis at 3,000 microg/ml has only 30% cytotoxicity on host cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Many plants and their components have been reported to have anti-EV71 activity (Kuo et al, 2009;Lin et al, 2009;Tsai et al, 2011;Zhu et al, 2011). As a traditional Chinese herbal medicine, the aerial part of S. chinensis (Lour.)…”
Section: Discussionmentioning
confidence: 99%
“…Many plants and their components have been reported to have anti-EV71 activity (Kuo et al, 2009;Lin et al, 2009;Tsai et al, 2011;Zhu et al, 2011). As a traditional Chinese herbal medicine, the aerial part of S. chinensis (Lour.)…”
Section: Discussionmentioning
confidence: 99%
“…Also, IC 50 value of K. gracilis leaf extract against EV71 and CVA16 were 35.88  μ g/mL and 42.91  μ g/mL, respectively (Figure 4), while the therapeutic index of K. gracilis leaf extract against EV71 and CVA16 ranged from 23 to 28. A literature survey indicated some extracts of Chinese herbs exhibiting anti-EV71 activities in vitro , such as Houttuynia cordata Thunb (IC 50 = 125.9  μ g/mL) [38], Woodfordia fruticosa Kurz (IC 50 = 1.2  μ g/mL) [34], Salvia miltiorrhiza (IC 50 = 585  μ g/mL) [39], Pueraria lobata (IC 50 = 0.028  μ g/mL) [40], and Glycyrrhiza uralensis (IC 50 = 0.056  μ g/mL) [41]. Therefore, K. gracilis leaf extract exhibited moderately potent anti- EV71 and CVA16 activities.…”
Section: Discussionmentioning
confidence: 99%
“…A. membranaceus, which has been frequently used with other TCMs in treatments for strengthening human immune responses (Xue et al, 2008), has been demonstrated to have antitumor effects in vitro and in vivo (Cho and Leung, 2007) and enhance the immunotherapeutic effects of type 1 diabetic mice (Li et al, 2007). The effects of G. uralensis include suppressing RANTES secretion by influenza H1N1 virus-infected A549 epithelial cells (Ko et al, 2006), inhibiting tumor growth without severe cytotoxicity to normal cells (Chung et al, 2001), and modulating immunity in macrophages and fibroblasts (Cheng et al, 2008;Kuo et al, 2009). C. foetida has versatile medical applications and is prescribed to ease uncomfortable feelings or medical symptoms caused by hot flashes, diabetes, inflammatory, HIV or malaria infection, osteoporosis, and vasoactive complications (Li and Yu, 2006).…”
Section: Trem-1 Tnf-mentioning
confidence: 99%